The knowledge of child abuse of future professionals in education: an exploratory study - Priegue Caamaño, Diana; Cambeiro Lourido, María del Carmen (Revista Complutense de Educación, 2015)
During the exercise of their activity, education professionals are well placed to make an early detection of child abuse and to identify possible risk cases. However, sometimes, teachers and educators in general claim lack of knowledge and training to perform these tasks. That is why, in this work we wish to insist on the necessity of analysing the training of future education professionals in child abuse, both within and outside the family, and regardless of whether it is caused by adults or other children. It should be noted that early identification of violent behaviour and, obviously, the implementation of strong prevention strategies presuppose good training in this sense. For this reason, we have performed a pilot study to analyse the formation that students of the degree in Pedagogy have on child abuse, using a questionnaire that we have designed specifically for such purpose. We carried out the pilot study of the instrument with a sample of 24 students (girls and boys) enrolled in the 4th year of the degree in Pedagogy. Among the conclusions reached we highlight that, after analysing the data derived from the pilot study, it can be concluded that future pedagogues consider this specific training necessary, because at present they consider it insufficient and too limited to cope with their professional responsibilities in the future.